Genotyping of Human Papillomavirus High Risk Type by High Resolution Melting Analysis - อุทัยวัตร ปรางทิพย์; ภูมิกอง อาภาพรรณ; สว่างวารี สุขุมาลย์; ธีระเจตกูล เยาวลักษณ์; จังตระกูล ดวงฤดี; ดาดวง จุรีรัตน์ (KKU Science Journal, 2015)
Human papillomavirus (HPV) is the major cause of cervical cancer, with high incidence as the second most common cancer of women in Thailand. The objective of this study is to develop the technique for identifying of high risk HPV types 16, 18, 45 and 58 by real-time PCR with high resolution melting analysis (HRM). DNA specimens were provided by National Cancer Institute. The quality of DNA was checked by housekeeping gene (beta actin) determination. Then, type specific primer of E6/E7 of HPV genes was used for DNA amplification. After using, SYBR Green staining, melting curve were analyzed for classification of HPV based on the difference of amplicon size and % GC contents in target genes. The entire assay time of HRM was 90 minutes compared to 4 hours of cervista technique. The detection limit of HRM assay for HPV type 16, 58 was 104 and for HPV type 18, 45 is 103 copies, respectively. No cross-reaction is observed. 34 known HPV genotype samples by cervista were subjected to HRM. The result showed that the sensitivity of HRM for HPV16 and HPV18 were 73.7% (n = 19) and 80% (n = 5), respectively. The specificity of HRM for HPV16 and HPV18 were 100% (n = 10) and 90% (n = 10), respectively. In summary, the developed technique is simply and rapid for detection of high risk HPV with high specificity.